A Hybrid Detection Method Based on Peroxidase-mediated Signal Amplification and Click Chemistry for Highly Sensitive Background-free Immunofluorescent Staining. (October 2019) - Antonov, Stanislav A.; Novosadova, Ekaterina V.; Kobylansky, Andrey G.; Tarantul, Vyacheslav Z.; Grivennikov, Igor A.
The copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction is increasingly used for detection of various macromolecules and metabolites in biological samples. Here, we present a detailed analysis of the CuAAC reaction conditions in cells and tissue sections. Using the optimized CuAAC conditions, we have devised a highly sensitive immunostaining technique, based on the tyramide signal amplification/catalyzed reporter deposition (TSA/CARD) method with a novel alkyne tyramide substrate. The described method offers improved detection threshold compared to conventional immunofluorescent staining and produces significantly lower non-specific background than TSA/CARD with fluorescent tyramides.